Morphological optimization of large-area arrays of TiO2 nanowires & nanotubes for enhanced cold field emission: experiment and theory1. Issue 25 (21st March 2015) - Choi, Mingi; Zhang, Zhuo; Chen, Jingkun; Deng, Zexiang; Yong, Kijung
<x xml:space="preserve">Abstract</x> Designed by finite elemental modelling, large-area arrays of TiO2 nanowires and nanotubes with differentiated heights mixed together are synthesized on a planar Ti wafer via hydrothermal methods.